Leveraging funds of knowledge to manage privacy practices in families. Issue 1 (18th October 2019) - Subramaniam, Mega; Kumar, Priya; Morehouse, Shandra; Liao, Yuting; Vitak, Jessica
ABSTRACT: Information and communication technologies play a critical role at home, school, and work for people of all ages. At the same time, use of these technologies can present challenges to privacy and security. In this study, we apply the concept of funds of knowledge to understand how families develop knowledge and skills around using technology and protecting personal information. Funds of knowledge explains how people gain knowledge and highlights how learning happens in a variety of environments beyond the classroom. Through interviews with 52 families living in economically disadvantaged communities in the United States, we develop a typology of privacy funds of knowledge in families. We also explore how privacy funds of knowledge inform families' privacy practices. We conclude the paper by identifying how these findings inform the development of resources for families to further enhance their digital practices.